Dog training alleviates PTSD symptomatology by emotional and attentional regulation. Issue 1 (1st January 2021) - Maoz, Inon; Zubedat, Salman; Dolev, Talya; Aga-Mizrachi, Shlomit; Bloch, Boaz; Michaeli, Yuval; Eshed, Yuval; Grinstein, Dan; Avital, Avi
ABSTRACT: Background: Post-Traumatic Stress Disorder (PTSD) symptoms include re-experiencing, avoidance, hyperarousal, and cognitive deficits, reflecting both emotional and cognitive dysregulation. In recent years, non-pharmacological approaches and specifically animal-assisted therapy have been shown to be beneficial for a variety of disorders such as Attention-Deficit/Hyperactivity Disorder, Autism Spectrum Disorder, and PTSD. However, little is mentioned in the literature about the reciprocal effects of the animal–human interaction. Objective: To evaluate the effects of a one-year dog training programme on PTSD symptomatology in youngsters with PTSD and on dogs' behaviour. Methods: Fifty-three adolescents, previously exposed to interpersonal trauma, were clinically diagnosed with PTSD and assigned to a dog-training programme group ( n = 30 ) and a control group ( n = 23 ) that engaged in other training programmes (e.g. cooking, hairstyling, etc.). Both groups were evaluated at baseline and following 12-months by The Clinician-Administered PTSD Scale for DSM-5 in Children and Adolescents (CAPS-CA-5) and Beck-Depression Inventory (BDI). Additionally, we physiologically measured both emotional and attention dysregulation. Results: Post-12-months training, a significant alleviation of PTSD symptomatology accompanied by lower depression severity was observed in the dog-training group, compared with a insignificant recovery in the control group. Furthermore, improved emotional and attentional regulation was observed in the dog-training group. Measuring the dogs' behaviour revealed increased anxiety and decreased selective attention performance, which was inversely correlated with the beneficial effects observed in the dog-training programme group. Conclusions: Our findings emphasize the role of emotional and attentional regulations on the dog–handler interface, as evidence-based support for the beneficial effects of the dog-training programme, as either a non-pharmacological intervention or as complementary to anti-depressants treatment of PTSD. Though pharmacological treatments increase the patients' well-being by treating certain PTSD symptoms, our suggested dog-training programme seems to influence the PTSD diagnostic status, thus may be implemented in civilians and veterans with PTSD. HIGHLIGHTS: One year of dog-training programme alleviated PTSD symptoms, defined as a change in CAPS-CA-5 diagnostic status, underlined by physiologically measured attention and emotional regulation. However, dog–human interaction resulted in the dogs' elevated anxiety and decreased attention.